The Extent of School Managers' Practicing of Leadership Styles according to the Managerial Grid Model in Al-Batinah North Governorate, Sultanate of Oman, and its relation to Job Satisfaction of Senior Teachers - algaraidih, mohamed suliman; Al-Kayoumi, Yousef Obeid (Advances in Social Sciences Research Journal, 2019)
The study aims at identifying the extent of school managers’ practicing of leadership styles according to the Managerial Grid Model in Al-Batinah North Governorate, Sultanate of Oman, and its relation to job satisfaction of senior teachers. .To achieve the study objective, a questionnaire consisting of (54) items distributed to (5) key areas, was administrated to (400) senior teachers after verifying its validity and reliability. The study reached a number of findings: the extent of school managers' practicing of leadership styles according to the Managerial Grid Model in Al-Batinah North Governorate, Sultanate of Oman is high and there were no statistically significant differences at the level of (α≤0.05) in the extent of school managers' practicing of leadership styles according to the Managerial Grid Model in Al-Batinah North Governorate, Sultanate of Oman due to the gender variable. The results also indicate that there is a direct relation between the type of leadership style adopted by the school managers and the level of satisfaction among teachers. The study introduces some recommendations: school managers should avoid raising differences among teachers while dealing with them as well as teachers should not be hesitated when taking administrative decisions, and should be involved in making these decisions.